Asset Turnover, Capital Structure and Financial Performance Consumption Industry Company in Indonesia Stock Exchange - Nurlaela, Siti; Mursito, Bambang; Kustiyah, Eny; Istiqomah, Istiqomah; Hartono, Sri (International Journal of Economics and Financial Issues, 2019)
This research is conducting an empirical test on the effect of capital structure, liquidity, asset structure and asset turnover on the financial performance of consumption industry sector companies in the Indonesia Stock Exchange in 2016-2018. The difference with previous research lies in the use of independent variables, the number of samples used and the study period. This research is quantitative research. The analytic method in this research is multiple linear regression analysis. The results of the t-test hypothesis show that the capital structure variable (DER), liquidity (CR), and asset turnover (TATO) have a significant effect on financial performance (ROA). Keywords: Capital Structure, Asset Turnover, Return on Assets JEL Classification: G3 DOI: https://doi.org/10.32479/ijefi.8185